A1.29 In rheumatoid arthritis, smoking is not primarily associated with anti-citrullinaged protein antibodies, but with the presence of several autoantibodies. (31st January 2014) - Muhammad, Ammar; van Wesemael, Tineke; Kochi, Yuta; Mjaavatten, Maria D; Wevers-de Boer, Kirsten; Allaart, Cornelia F; Trouw, Leendert A; Suzuki, Akari; Yamamoto, Kazuhiko; van der Helm-van Mil, Annette H M; Huizinga, Tom W J; Toes, René E M; et al.
Abstract : Background and Objectives: In rheumatoid arthritis (RA), smoking has been described to be specifically associated with the presence of anti-citrullinated protein antibodies (ACPA). However, smoking has also been shown to be associated with the presence of autoantibodies in various other autoimmune diseases, such anti-dsDNA in systemic lupus erythematosus and anti-Jo1 in idiopathic inflammatory myopathy. We therefore investigated whether smoking is specifically associated with ACPA-positive RA, or with autoantibody-positive RA in general. Materials and Methods: A meta-analysis was performed using RA patients from 5 countries: Norway, the Netherlands, Japan, Sweden, and the United Kingdom. Complete data on rheumatoid factor (RF)-, ACPA-status and tobacco exposure were available for 6320 RA patients. The odds ratios (ORs) and 95% confidence intervals (95% CIs) associated with the presence of RF, ACPA or both, were calculated by logistic regression comparing ever smokers with never smokers, and using the RF-negative ACPA-negative RA patients as the reference category. Results: There was no significant association between smoking and RA in patients who were positive for only one antibody, being either RF (OR 1.04, 0.76 – 1.42) or ACPA (OR 1.00, 0.82 – 1.22). However, smoking was significantly associated with double-positive (RF-positive and ACPA-positive) RA (OR 1.55, 1.20 – 2.00). When ANA-status was also taken into account in the Dutch cohort, the association with smoking was strongest for the triple-positive group (OR = 2.43, 95% CI 1.47 – 4.00), although the difference with the double-positive RA patients (RF- and ACPA-positive, ANA-negative) (OR = 1.73, 95% CI 1.14 – 2.62) was not statistically significant. Conclusions: Smoking is not specifically associated with ACPA-positive RA, but rather with the concurrent presence of RF and ACPA in RA patients. These data indicate that smoking predisposes to the development of several autoantibodies, and that current hypotheses about the role of smoking in the pathophysiology of RA may need to be revisited.